PENGARUHENVIRONMENTAL PERFORMANCE DAN MEKANISMECORPORATE GOVERNANCE TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Puji Handayati (Jurnal Akuntansi Aktual, 2015)
Abstract: Triple Bottom Lines Concept explain that corporation did not only responsible for financial performance like in single bottom line, but also concerned in social and environmental performance. It means factors that affecting corporate social responsibility disclosure have to be known. This research is going to know the effect of environmental performance variable proxy with corporate environmental performance that measured with PROPER. Good environmental performance will motivate corporation to increase corporate social responsibility (CSR). And corporate governance mechanism variable thatproxies with institutional possession, commissioner board, independent commissioner board, and audit committee. Good Corporate Governance will motivate corporation to disclose CSR. Corporate Social Responsibility Disclosure (CSRD) using Global Reporting Intiative (GRI) indicator. Research designwas asosiatif kausalitas. The population were 154 manufacture companies that listed in Bursa Efek Indonesia periode 2009–2011. For its sample, this research used purposive sampling obtained 11 companies. And the method of data analysis used multiple linear regression. The result analysis showed that environmental performance and audit committee have positive significant influence on CSRD while corporate governance mechanism that proxies with institutional possession and independent commissioner board did not influence CSRD. It showed that higher environmental performance followed with increased CSRD and better monitoring mechanism to management would create good corporate governance that motivate to do CSRD.Keywords: environmental performance, corporate governance mechanism, Corporate Social Responsibility Disclosure (CSRD)